A comprehensive review on Citrus macroptera Mont. - Dhar, Arunima; Bala, Esha; Chetri, Bimal K; Singha, Siddhartha (Ethnobotany Research and Applications, 2025)
Background: Citrus macroptera, a member of the Citrus genus, holds significant potential for therapeutic applications due to its diverse pharmacological properties and biological activities. This review delves into the plant’s taxonomy, morphology, and traditional uses, highlighting its role in various medicinal and culinary practices. The study focuses on the three main parts of the plant – fruit, leaves, and stem – and explores their wide range of pharmacological properties. These include antioxidant, cytotoxic, antimicrobial, thrombolytic, hypoglycemic, anxiolytic, anti-depressant, cardioprotective, and hepatoprotective activities which are proven in clinical studies. Methodology: A systematic search was done from relevant databases with keywords related to the study. Result: The presence of phenolic acids, flavonoids, and tannins, acting synergistically as antioxidants, contributes significantly to these properties. The benefits of various plant parts extracts are also examined in the review. Notably, the fruit peel extract causes premature death to non-small cell lung cancer cells through prooxidant-induced apoptosis. Animal studies indicate that the fruit possesses an antioxidant capacity against acetaminophen-induced hepatonephrotoxicity as well as moderate α-amylase inhibitory activity and hypoglycemic effects in normal and glucose induced hyperglycaemic rats respectively. Conclusion: C. macroptera could be a potential oral hypoglycemic agent source in vitro. This detailed review explores C. macroptera belonging to the Citrus genus, which has a wide range of pharmacological properties and diverse biological activities and hence may have significant therapeutic potential. The taxonomic classification, morphology, and traditional uses of this plant over time in various medicinal and culinary practices will be discussed. Keywords: Citrus macroptera, Phytochemicals, Antioxidants, Antimicrobial agents, Traditional medicine, Therapeutic uses